(untitled) (Journal of Misan Researches, 2024)
Sheikh Ahmed Al-Waeli is an encyclopedia of knowledge and literature at the same time. Our research came to reveal some stylistic characteristics through analyzing a poetic text full of semantics, which is a poem (To Abi Turab). It has been shown that the creator conjugates between the requirements of the mind and the needs of the soul, through the dominance of a number of stylistic dominances, such as contrasts, the dominance of the praised and the creator self, indirect textuality as well as the stylistic features, which were represented by the choice of words with phonetic sides, or the combination of two hamzas, and other characteristics.